An Ordinance Prohibiting the Unlawful Carrying of Arms, DAILY DEMOCRATIC STATESMAN, May 29, 1880, at 4 (Austin, TX) §3 - (:unkn) unknown (My University, 1880)
Any person violating §§ 1-2 above may be arrested without a warrant, and any policeman who shall fail to or refuses to arrest such person on his own knowledge or upon information, shall be fined not exceeding one hundred dollars.
Keywords: PEACE OFFICERS